Climate Change Perspective: The Advantage and Disadvantage of COVID-19 Pandemic - Oo, Kyaw Than; Thin, Moh Moh Zaw (Journal of Sustainability and Environmental Management, 2022)
Government initiatives during the COVID-19 outbreak had a significant impact on global energy consumption patterns. Many international borders were blocked, and individuals were confined to their homes, restricting mobility and changing social habits. The lockdowns introduced economic, physical, and social pastimes to a halt. However, as an advantage, the world had a good effect on air quality, the environment, and greenhouse gases (GHGs), in particular CO2 emissions. When compared to the mean 2019 levels, daily worldwide CO2 emissions had fallen by –17 % (–11 to –25 % for 1) by early April 2020, with changes in surface transportation accounting for little under half of the decline. The total global CO2 reduction from January to April 2020 was predicted to be more than 1749 Mt CO2 (a 14.3 % decline), with the transportation sector contributing the most (58%) followed by coal power generation (29%), and industry (10%). As a result, transportation was identified as the primary source of more than half of the emissions reduction during the epidemic. As of August 23, 2021, 193 countries produced 8.4 million tons of pandemic-related plastic waste, with 25.9 thousand tons dumped into the ocean, accounting for 1.5 percent of total riverine plastic discharge globally. As a result of China and India’s record-breaking confirmed cases, MMPW generation and discharge are projected to be more skewed toward Asia. The study found that hospital trash accounts for 73% of global discharge and that Asia accounts for 72% of global discharge, indicating the need for better medical waste management in emerging countries. This review highlights the brief lessening in GHG outflows and expanded request for single-use plastics, including the weight of an as of now out-of-control worldwide plastic squander emergency caused by the COVID-19 widespread. This review also will be helpful for people to understand the COVID-19 impact on climate change point of view. There is advantage and disadvantage brought by this pandemic and it’s the best time to change the new normal of globalization. Global policies makers should consider the acute need to change the policies for a circular economy with the best environment sustainable, both during the pandemic and, more significantly, thereafter. The authors of the reference articles on the COVID-19 pandemic hope their findings will aid attempts to better understand the disease’s relationship to climate change. If lessons from both global crises are learned, the world may be better prepared to deal with global climate change, which has local consequences.